EFFICACY OF LABORATORY PREPARED WETTABLE POWDER FORMULATION OF ENTOMOPATHOGENOUS FUNGI BEAUVERIA BASSIANA, METARHIZIUM ANISOPLIAE AND PAECILOMYCES FUMOSOROSEUS AGAINST THE POLYPHAGOTARSONEMUS LATUS (BANK) (ACARI: TARSONEMIDAE) (BROAD MITE) ON CAPSICUM ANNUM (CHILLI) - Ihsan Nugroho,; Yusof bin Ibrahim, (Tropical Life Sciences Research, 2007)
The efficacies of wettable powder (WP) formulations of Beauveria bassiana (BbGc), Paecilomyces fumosoroseus (PfPp) and Metarhizium anisopliae (MaPs) as a single or combined treatments against the Polyphagotarsonemus latus (Bank) (Acari: Tarsonemidae) (broad mite) and its damage on one month old Capsicum annum (chilli) plants were compared with the acaricide amitraz in the field. The WP formulations were applied at four spray intervals on the chilli shoots at the rate of 1 × 1010 conidia ml-1. Both B. bassiana and P. fumosoroseus significantly reduced the mite population and subsequently resulted in a high percentage of shoot recovery by the fourth spray compared with the control. Combined treatments of M. anisopliae and P. fumosoroseus, and M. anisopliae and B. bassiana could not adequately suppress mite population hence comparatively more shoots were infested. New shoots treated with B. bassiana resulted in excellent recovery (93.33% shoot protection) which was not significantly different from that of amitraz (96.67%). Amitraz could suppress the mite population faster whereby zero level of mite population was achieved after the second spraying. Nevertheless, WP formulation of B. bassiana as a miticide was as effective as amitraz against the broad mites. Efikasi formulasi serbuk basah (WP) Beauveria bassiana (BbGc), Paecilomyces fumosoroseus (PfPp) dan Metarhizium anisopliae (MaPs) sebagai rawatan tunggal atau campuran ke atas Polyphagotarsonemus latus (Bank) (Acari: Tarsonemidae) (hamama lebar) dan kerosakannya terhadap Capsicum annum (pokok cili) berumur satu bulan telah dibandingkan dengan racun hamama amitraz di lapangan. Kesemua formulasi WP itu telah disembur berselangan empat kali ke atas pucuk cili pada kadar 1 × 1010 konidia ml-1. Kedua-dua B. bassiana dan P. fumosoroseus didapati mengurangkan populasi hamama secara signifikan dan seterusnya menghasilkan peratus pemulihan pucuk yang tinggi selepas semburan keempat berbanding dengan rawatan kawalan. Rawatan campuran M. anisopliae dan P. fumosoroseus, dan M. anisopliae dan B. bassiana tidak dapat menindas populasi hamama dengan memuaskan, oleh itu secara bandingannya lebih banyak pucuk telah diserang. Pucuk baru yang dirawat dengan B. bassiana menghasilkan pemulihan yang sungguh baik (93.33% perlindungan pucuk) dengan perbezaan yang tidak signifikan berbanding amitraz (96.67%). Amitraz lebih pantas menindas populasi hamama, iaitu kepupusan populasi hamama dicapai selepas semburan kedua. Walau bagaimanapun, formulasi WP B. bassiana sebagai mitisid adalah sama-sama berkesan dengan amitraz ke atas hamama lebar.